Safety and effectiveness of double microcatheter technique in the treatment of ruptured aneurysms of anterior cerebral circulation - Zhao, Xintong; Zhang, Zihuan; Liu, Jiaqiang; Qin, Feiyun; Hu, Liying; Li, Zhenbao (Frontiers in Neurology, 2022)
Objective：To evaluate the safety and effectiveness of double microcatheter technique in the treatment of ruptured aneurysms of anterior cerebral circulation. Methods: Between 2012 and 2019, 113 patients with ruptured aneurysms in anterior cerebral circulation were treated by double microcatheter technique. Clinical records, angiographic results, procedure-related complications were reviewed. Clinical and angiographic follow-up was performed. Results: Complete occlusion, neck remnant and partial occlusion were achieved in 56.6%, 38.9% and 4.4% in the whole procedures, respectively. The incidence of intraoperative complications was 5.3% (6/113). The overall rate of morbidity was 10.6% (12/113). Three patients (2.7%) died before discharge. There was no procedure-related mortality. The favorable outcomes were obtained in 79.6% (90/113) of the whole patients at discharge. High Hunt-Hess grad and suffering from craniotomy or external ventricular drainage were risk factors for clinical outcomes at discharge. Ninety-one patients received clinical follow-up at a mean interval of 14.07±11.68 months. Favorable outcomes were obtained in 92.3% (84/91) patients at follow-up. Angiographic follow-up was performed in 66 patients at an average of 11.53±11.13 months. The recurrence rate is 37.9%. Thirteen of them (19.7%) received retreatment. Conclusion: Double microcatheter technique can be performed in ruptured aneurysms with high technical success and low morbidity/mortality. Recurrence remains a problem. Patients should be followed up regularly.